SISTEM INFORMASI U-ACTIVE PADA SMK AL-KAHFI BERBASIS WEB UNTUK MENGEVALUASI KETERCAPAIAN KURIKULUM SETIAP GURU - Absorihim; Nawassyarif; Yana Kharisma (Program Studi Informatika Universitas Teknologi Sumbawa, 2019)
Al-Kahfi Vocational School is the pesantren based school which is expected to become one of the pilot schools as well as the guidance and needs of the community, but in Al-Kahfi Vocational teaching process is still fairly common, by the way the teacher comes and fills in attendance then starts teaching according to schedule, and when the teaching time is up, the teacher is welcome to go home. Based on this process, school stakeholders find it difficult to see curriculum achievements. Therefore an information system is needed to evaluate the curriculum achievements of each teacher. This study aims to build an information system for curriculum achievement of each web-based instructor. Where this system was developed using the PHP programming language by using MySQL as a database. The software development method uses the Waterfall method. Software testing is done through black-box testing, data collection techniques in this study using observation, interviews, and literature study. The final result obtained is an information system on the achievement of the curriculum of each web-based instructor who is able to provide convenience in evaluating the curriculum achievement of each teacher